2019
DOI: 10.1146/annurev-control-060117-105206
|View full text |Cite
|
Sign up to set email alerts
|

Internal Models in Biological Control

Abstract: Rationality principles such as optimal feedback control and Bayesian inference underpin a probabilistic framework that has accounted for a range of empirical phenomena in biological sensorimotor control. To facilitate the optimization of flexible and robust behaviors consistent with these theories, the ability to construct internal models of the motor system and environmental dynamics can be crucial. In the context of this theoretic formalism, we review the computational roles played by such internal models an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
143
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 134 publications
2
143
0
Order By: Relevance
“…At one extreme, Lum et al (2005) have suggested that variability may be a trial-and-error process for finding successful behaviors. At the other, McNamee and Wolpert (2019) have proposed that animals may develop internal computational models of the biomechanics governing their own bodies and the environment so as to generate optimal behavior. The results of this paper suggest a different framework in which behavior is constantly shaped by sensory feedback, and animals use this to find a "good enough" solution to most problems (Loeb, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…At one extreme, Lum et al (2005) have suggested that variability may be a trial-and-error process for finding successful behaviors. At the other, McNamee and Wolpert (2019) have proposed that animals may develop internal computational models of the biomechanics governing their own bodies and the environment so as to generate optimal behavior. The results of this paper suggest a different framework in which behavior is constantly shaped by sensory feedback, and animals use this to find a "good enough" solution to most problems (Loeb, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Internal models of target motion are necessary to overcome visual delays inherent to the visuomotor system but also for instances of target occlusion and interceptive movements (Becker and Fuchs, 1985;Bosco et al, 2015). These internal models are useful as they allow the brain to minimize prediction error and behave optimally in the environment (McNamee and Wolpert, 2019). Notably, the eye position signals decoded from visual areas such as MT, MST, VIP, and LIP lead the current eye position, indicating a predictive process based on an efference copy of eye position (Dowiasch et al, 2016).…”
Section: Underlying Neurophysiology For Predictionmentioning
confidence: 99%
“…The production of desired movements with a novel tool involves forming the internal representation of mechanical properties of the tool interacting with the body, which is so called the internal model . Our finding of the incomplete adaptation to novel dynamics of the piano key in patients with FTSD therefore suggests an impairment of updating the internal model of the piano‐key dynamics.…”
Section: Discusssionmentioning
confidence: 84%
“…A key skill indispensable for the dexterous use of various tools is a flexible adaptation to novel mechanical dynamics emerging from contact of a body with the tool. Successful adaptation requires representing mechanical properties of the object based on somatosensory afferent information, which enables the nervous system to elicit motor commands necessary for the production of desired movements, so called internal models . However, some neurological disorders such as cerebellar ataxia and Huntington's disease impair the formation of such representation, which prevents an adaptation to novel dynamics in dexterous tool use.…”
mentioning
confidence: 99%